A titanium-iron hydrogen storage alloy and a preparation method thereof
By introducing multi-alloy elements such as Mn, Cr and La into the iloxane hydrogen storage alloy, the element composition is optimized, and the problems of high activation temperature and poor anti-toxicity are solved, and the alloy is efficiently stored and good performance is achieved.
Patent Information
- Application Number
- CN202411779401.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
AI Technical Summary
The activation temperature of iloxane hydrogen storage alloy is high and has poor anti-toxicity, which affects its application efficiency and safety.
By introducing multi-alloy elements such as Mn, Cr and La into the iloxane hydrogen storage alloy, the element composition is adjusted to Ti1.04La0.01Fe1-x-yMnxCr to optimize the microstructure and performance of the alloy.
It has achieved direct hydrogen absorption at relatively mild temperatures and pressures, good activation performance, improved hydrogen storage, and improved cycle stability and mechanical properties.
Smart Images

Figure CN119753479A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage alloys, and in particular to a titanium-iron series hydrogen storage alloy and a preparation method thereof. Background Art
[0002] In the context of global energy transformation, hydrogen energy, as an important carrier of clean energy, is gradually becoming a hot spot pursued by different industries. However, the commercial application of hydrogen energy still faces multiple challenges such as high cost and immature storage and transportation technology. There are three main ways to store hydrogen: high-pressure gas storage, liquid hydrogen storage and metal hydride storage. Although high-pressure gas and liquid hydrogen storage technologies are relatively mature, their costs and safety still need to be further optimized. Metal hydride hydrogen storage technology, especially titanium-iron hydrogen storage alloys, has the advantages of easy availability of materials and the ability to absorb / release hydrogen at room temperature, and is considered to be a potential hydrogen storage material.
[0003] Secondly, titanium-iron hydrogen storage alloys not only have a large hydrogen storage capacity (its hydrogen storage capacity can reach 1.8%), but also absorb and release hydrogen quickly. These advantages are very beneficial to its practical application. However, titanium-iron hydrogen storage materials also have some disadvantages, such as difficulty in activation (must be heated to above 250°C for repeated hydrogen filling-evacuation operations) and poor resistance to poisoning. In order to improve these shortcomings, performance optimization can be achieved through alloying elements such as Mn and Co. In addition, although the cost of titanium-iron alloys is relatively low, in order to meet the needs of larger-scale commercial applications, it is still necessary to further reduce costs while improving performance.
[0004] Therefore, it is necessary to provide a titanium-iron hydrogen storage alloy with good dynamic properties. Summary of the invention
[0005] In order to solve the problem of high activation temperature of titanium-iron hydrogen storage alloy in the prior art, the present invention provides a titanium-iron hydrogen storage alloy and a preparation method thereof.
[0006] In order to solve the above technical problems, one of the purposes of the present invention is to provide a titanium-iron hydrogen storage alloy, wherein the element composition of the titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 1-x-y Mn x Cr y ;
[0007] Wherein x and y represent the atomic percentages of Mn and Cr, respectively, 0.1≤x≤0.2, 0.01≤y≤0.06.
[0008] The titanium-iron hydrogen storage alloy provided by the present invention adopts multi-element substitution. Due to the interaction between the multi-element alloy elements, the alloy maintains excellent activation performance while improving the hydrogen storage capacity to a certain extent. The present invention has found through research that under multi-element substitution of manganese (Mn), chromium (Cr) and lanthanum (La) based on the titanium-iron system, when the percentage of Ti atoms is higher than 1.04, the activation performance and the maximum hydrogen storage capacity of the prepared hydrogen storage alloy will decrease to varying degrees, and under this multi-element substitution, the addition of manganese helps to improve the cyclic stability of the alloy, so that the alloy maintains good performance during repeated absorption and release of hydrogen. The addition of chromium can increase the specific surface area and porosity of the alloy, providing more active sites for the adsorption of hydrogen. At the same time, the addition of chromium can also form some defects and vacancies, which are conducive to the diffusion and transmission of hydrogen atoms, thereby improving the hydrogen storage efficiency of the alloy. In addition, the specific amount of lanthanum added to the alloy forms complex compounds or solid solutions with main elements such as titanium and iron, providing more active sites for the storage of hydrogen, and the addition of a specific amount of lanthanum makes the grains of the alloy refined and the grain size more uniform, thereby improving the mechanical properties and thermal stability of the alloy.
[0009] The x in the present invention is 0.05-0.15, and the x can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable;
[0010] The y described in the present invention is 0.01-0.06, and the y can specifically be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; preferably, the y=0.02.
[0011] In one embodiment, the titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.92 Mn 0.07 Cr 0.01 .
[0012] In one embodiment, the titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 .
[0013] In one embodiment, the titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.85 Mn 0.11 Cr0.04 .
[0014] In one embodiment, the titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.85 Mn 0.09 Cr 0.06 .
[0015] The second object of the present invention is to provide a method for preparing the titanium-iron hydrogen storage alloy as described above, the preparation method comprising the following steps:
[0016] (1) weighing elemental metals according to atomic ratio and mixing them to obtain a mixed material;
[0017] (2) Smelting the mixed material obtained in step (1) and obtaining an alloy ingot after cooling.
[0018] In one embodiment, step (2) further comprises: turning over the alloy ingot and repeatedly smelting 2 to 4 times;
[0019] Preferably, the repeated smelting in step (2) is performed three times.
[0020] In the present invention, the flipping and repeated melting are adopted, so that the component elements in the alloy can be more evenly distributed inside the alloy, which helps to reduce the segregation phenomenon in the alloy and improve the overall performance of the alloy. At the same time, the grains of the alloy can be refined and its microstructure can be improved. The refinement of the grains can improve the mechanical properties and hydrogen storage properties of the alloy. In addition, the pores and inclusions in the alloy can be reduced, and the density of the alloy can be improved. The improvement of the density can make the alloy have better mechanical properties and hydrogen storage capacity.
[0021] In one embodiment, the smelting in step (2) is carried out in a suspension furnace under a protective atmosphere;
[0022] Preferably, the protective atmosphere is an argon atmosphere.
[0023] In one embodiment, the purity of the elemental metal in step (1) is ≥ 99.5 wt%.
[0024] In one embodiment, the cooling in step (2) further includes a crushing process;
[0025] The average particle size of the titanium-iron hydrogen storage alloy obtained after crushing is 40 to 100 meshes.
[0026] Based on the above, compared with pure ferro-titanium alloy, the ferro-titanium hydrogen storage alloy provided by the present invention does not require special activation treatment, can directly absorb hydrogen at relatively mild temperature and pressure, and has good activation performance; the alloy has good dynamic performance.
[0027] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 Ti prepared in Example 1 1.04 La 0.01 Fe 0.92 Mn 0.07 Cr 0.01 Activation curves of hydrogen storage alloys;
[0030] Figure 2 Ti prepared in Example 2 1.04 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 Activation curves of hydrogen storage alloys;
[0031] Figure 3 Ti prepared in Example 3 1.04 La 0.01 Fe 0.85 Mn 0.11 Cr 0.04 Activation curves of hydrogen storage alloys;
[0032] Figure 4 Ti prepared in Example 4 1.04 La 0.01 Fe 0.85 Mn 0.09 Cr 0.06 Activation curves of hydrogen storage alloys;
[0033] Figure 5 The PCT curves of hydrogen absorption and desorption of the hydrogen storage alloys prepared in Examples 1-4 at 303K and 5MPa;
[0034] Figure 6 Ti prepared in Example 5 1.04 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02Activation curves of hydrogen storage alloys;
[0035] Figure 7 Ti prepared in Comparative Example 1 0.99 La 0.01 Fe 0.85 Mn 0.13 Cr 0.02 Activation curves of hydrogen storage alloys;
[0036] Figure 8 Ti prepared in Comparative Example 2 1.02 La 0.01 Fe 0.88 Mn 0.09 Cr 0.03 Activation curves of hydrogen storage alloys;
[0037] Fig. 9 Ti prepared in Comparative Example 3 1.02 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 Activation curves of hydrogen storage alloys;
[0038] Fig.10 The PCT curves of hydrogen absorption and desorption of the hydrogen storage alloys prepared in Comparative Examples 1-3 at 303K and 5MPa. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0040] In the description of the present invention, it should be noted that all terms used in the present invention (including technical terms and scientific terms) have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and cannot be understood as limiting the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in the present invention.
[0041] Example 1
[0042] Hydrogen storage alloy Ti 1.04 La0.01 Fe 0.92 Mn 0.07 Cr 0.01 Weigh 150g of raw materials according to the weight percentage determined by the alloy formula. The purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0043] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0044] The sample was crushed to 80 mesh, and then 1.75g of the sample was placed in the sample chamber. The sample chamber was evacuated at 333K for 1 hour, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen, and the hydrogen storage capacity after activation for 30 minutes could reach 1.17wt.%. The sample chamber was evacuated at 303K for 1 hour, and then filled with 5MPa hydrogen until the alloy was fully activated. Figure 1 and Figure 5 As shown, the maximum hydrogen storage capacity of the alloy measured at 303K and 5MPa is 1.66wt.%.
[0045] Example 2
[0046] Hydrogen storage alloy Ti 1.04 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 Weigh 150g of raw materials according to the weight percentage determined by the alloy formula. The purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0047] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0048] The sample was crushed to 80 mesh, and then 1.75g of the sample was taken and placed in the sample chamber. The sample chamber was evacuated at 333K for 1 hour, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen, and the hydrogen storage capacity after activation for 30 minutes could reach 1.50wt.%. The sample chamber was evacuated at 303K for 1 hour, and then filled with 5MPa hydrogen until the alloy was fully activated. Figure 2 and Figure 5As shown, the maximum hydrogen storage capacity of the alloy measured at 303K and 5MPa is 1.81wt.%.
[0049] Example 3
[0050] Hydrogen storage alloy Ti 1.04 La 0.01 Fe 0.85 Mn 0.11 Cr 0.04 Weigh 150g of raw materials according to the weight percentage determined by the alloy formula. The purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0051] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0052] The sample was crushed to 80 mesh, and then 1.75g of the sample was placed in the sample chamber. The sample chamber was evacuated at 333K for 1 hour, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen, and the hydrogen storage capacity after activation for 30 minutes could reach 1.66wt.%. The sample chamber was evacuated at 303K for 1 hour, and then filled with 5MPa hydrogen until the alloy was fully activated. Figure 3 and Figure 5 As shown, the maximum hydrogen storage capacity of the alloy measured at 303K and 5MPa is 1.71wt.%.
[0053] Example 4
[0054] Hydrogen storage alloy Ti 1.04 La 0.01 Fe 0.85 Mn 0.09 Cr 0.06 Weigh 150g of raw materials according to the weight percentage determined by the alloy formula. The purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0055] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0056] The sample was crushed to 80 mesh, and then 1.75g of the sample was taken and placed in the sample chamber. The sample chamber was evacuated at 333K for 1 hour, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen, and the hydrogen storage capacity after activation for 30 minutes could reach 1.64wt.%. The sample chamber was evacuated at 303K for 1 hour, and then filled with 5MPa hydrogen until the alloy was fully activated. Figure 4 and 5 As shown, the maximum hydrogen storage capacity of the alloy measured at 303K and 5MPa is 1.68wt.%.
[0057] Example 5
[0058] Hydrogen storage alloy Ti 1.04 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 Weigh 150g of raw materials according to the weight percentage determined by the alloy formula. The purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0059] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0060] The sample was crushed into 80 mesh, and then 1.75g of the sample was taken and placed in the sample chamber. The sample chamber was evacuated at 323K for 1 hour, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen, and the hydrogen storage capacity after 30 minutes of activation could reach 1.67wt.%. It can be seen that the sample provided in this embodiment, especially during the second activation, can be suitable for a lower activation temperature and has a better activation effect than the higher activation temperature of Example 2. Evacuate the chamber at 303K for 1 hour, and then fill it with 5MPa hydrogen until the alloy is fully activated. Figure 6 As shown, the maximum hydrogen storage capacity of the alloy measured at 303K and 5MPa is 1.82wt.%.
[0061] Comparative Example 1-2
[0062] Comparative Example Ti 0.99 La 0.01 Fe 0.85 Mn 0.13 Cr 0.02 Comparative Example Ti 1.02 La0.01 Fe 0.88 Mn 0.09 Cr 0.03 150g of raw materials are weighed according to the weight percentage determined by the alloy formula, and the purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0063] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0064] The sample was crushed to 80 mesh, and then 1.75g of the sample was placed in the sample chamber. The sample chamber was evacuated at 333K for 1 hour, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen. The sample chamber was evacuated at 303K for 1 hour, and then filled with 5MPa hydrogen until the alloy was fully activated.
[0065] The hydrogen storage alloys prepared in Comparative Examples 1 and 2 were tested, and the test results are as follows: Figure 6 , 7 As shown in Figure 9. As can be seen from the figure, when Ti is not excessive, the alloy can react with hydrogen for the first time, but the reaction rate is slow. After the second time, the alloy can directly and quickly react with hydrogen, and the hydrogen storage capacity after activation for 30 minutes is 1.56wt.% and 1.25wt.%, respectively. At room temperature, the maximum hydrogen storage capacity of the alloy is 1.69wt.%. When Ti is in excess of 0.03, the alloy can also react with hydrogen for the first time, and the maximum hydrogen storage capacity of the alloy at room temperature is 1.67wt.%, see Figure 7 , Figure 8 and Fig.10 .
[0066] When the Ti content in the comparative example is not excessive and is 0.03 in excess, compared with the Ti content of 0.05 in excess, the activation performance of the alloy and the hydrogen storage capacity of the alloy at room temperature are not significantly improved.
[0067] Comparative Example 3
[0068] Comparative Example Ti 1.02 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 Weigh 150g of raw materials according to the weight percentage determined by the alloy formula. The purity of the metal element used in the experiment is above 99.5%. The preparation method of the hydrogen storage alloy is as follows:
[0069] The above raw materials are placed in an induction suspension melting furnace in order of melting point, and are melted under argon atmosphere protection after vacuum exhaust. To ensure uniform composition of the alloy, an alloy ingot is obtained after cooling. The alloy ingot is turned over and melted repeatedly for 3 times.
[0070] The sample was crushed to 80 mesh, and then 1.75g of the sample was placed in the sample chamber. The sample chamber was vacuumed at 333K for 1h, and then filled with 5MPa hydrogen. The absorption and release of hydrogen were repeated twice. The alloy could react with hydrogen for the first time, but the reaction rate was slow. After the second time, the alloy could directly and quickly react with hydrogen, and the hydrogen storage capacity after activation for 30min could reach 1.54wt.%. The sample chamber was vacuumed at 303K for 1h, and then filled with 5MPa hydrogen until the alloy was fully activated. See Fig. 9 and Fig.10 .
[0071] Compared with Example 2, when the ratio of La, Fe, Mn and Cr remains unchanged and Ti is in excess of 0.03, the initial activation performance is slightly better than that of Example 2, and the maximum hydrogen storage capacity is lower than that of Example 2, which is 1.75wt.%.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A titanium-iron hydrogen storage alloy, characterized in that: The element composition of the titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 1-x-y Mn x Cr y ; Wherein x and y represent the atomic percentages of Mn and Cr, respectively, 0.1≤x≤0.2, 0.01≤y≤0.
06.
2. The titanium-iron hydrogen storage alloy according to claim 1, characterized in that The titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.92 Mn 0.07 Cr 0.01 .
3. The titanium-iron hydrogen storage alloy according to claim 1, characterized in that: The titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.87 Mn 0.11 Cr 0.02 .
4. The titanium-iron hydrogen storage alloy according to claim 1, characterized in that: The titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.85 Mn 0.11 Cr 0.04 .
5. The titanium-iron hydrogen storage alloy according to claim 1, characterized in that: The titanium-iron hydrogen storage alloy is Ti 1.04 La 0.01 Fe 0.85 Mn 0.09 Cr 0.06 .
6. A method for preparing a titanium-iron hydrogen storage alloy according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) weighing elemental metals according to atomic ratio and mixing them to obtain a mixed material; (2) Smelting the mixed material obtained in step (1) and obtaining an alloy ingot after cooling.
7. The preparation method according to claim 6, characterized in that: Step (2) further comprises: turning over the alloy ingot and repeatedly smelting the alloy ingot 2 to 4 times; Preferably, the repeated smelting in step (2) is performed three times.
8. The preparation method according to claim 6, characterized in that: The smelting in step (2) is carried out in a suspension furnace under a protective atmosphere; Preferably, the protective atmosphere is an argon atmosphere.
9. The preparation method according to claim 6, characterized in that: The purity of the elemental metal in step (1) is ≥99.5wt%.
10. The preparation method according to claim 6, characterized in that: Step (2) further comprises a crushing process after cooling; The average particle size of the titanium-iron hydrogen storage alloy obtained after crushing is 40 to 100 meshes.